KUALITAS PELAYANAN DALAM MENINGKATKAN KEPUASAN PELANGGAN PT TOGU PANCING BANJARMASIN - Rika Sylvia; Masrifani Masrifani; Rahayu Septiani (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2022)
The purpose of this study was to determine the quality of service that has been provided by PT Togu Pancing and to determine the appropriate quality of service in increasing customer satisfaction of PT Togu Pancing. The type of research used is descriptive qualitative, where the population in this study is all customers of PT Togu Pancing from January to June 2021 as many as 300 customers, while the sample is 30 customers. The result of this research is to implemet the five variables, especially for the Tangibles variable so that the company can meet the standards of the facilities provided, for example by adding or replacing old facilities with new ones so as to increase customer satisfaction. In the variables of Reliability, Responsiveness, Assurance and Emphty so that the company can improve the quality of its service, so that it will lead to customer satisfaction.